Oxigenoterapia en paciente femenina de 30 años con tuberculosis. - Ponce Espinoza, Maria Belén (2022)
Mycobacterium tuberculosis is the causative agent of the infection called pulmonary tuberculosis (TB), which produces pulmonary infection and is one of the most prevalent pathologies worldwide. We present the case of a 30-year-old female patient with a clinical picture characterized by cough, fatigue, loss of appetite, night sweats, unquantified temperature rise, dyspnea plus sputum with the presence of bloody streaks. The objective of this project was to determine the benefits of oxygen therapy in a 30-year-old female patient with tuberculosis. It was concluded that oxygen therapy by itself is not a treatment for tuberculosis, however it is of vital importance when signs of respiratory distress appear to correct hypoxemia. For this reason, it is necessary to carry out an exhaustive assessment of each patient in order to know how to identify the oxygen therapy system that fits their needs.